Autistic girls and school exclusion: Perspectives of students and their parents. (May 2017) - Sproston, Kelda; Sedgewick, Felicity; Crane, Laura
Background and aims: If a child's behaviour does not conform to school policy or causes harm to either peers or staff, they may be temporarily or permanently excluded from school. Whilst it is unlawful to exclude children due to their needs, school exclusion is common amongst children with special educational needs, including autism. Currently, little is known about experiences of school exclusion from the perspectives of autistic students and/or their parents. This is particularly the case for girls on the autism spectrum. Methods: Semi-structured interviews were conducted with eight autistic girls and their parents (seven mothers, one father). Interviews explored experiences of mainstream schooling; alternative educational provisions that were offered (if any); the school exclusion process; and the girls' current educational provision. As well as asking the girls and their parents about positive and negative aspects of their past and current experiences, participants were asked to reflect on areas for potential improvements. Results: Interviews were analysed using thematic analysis and three key themes emerged from the data: inappropriate school environments (including problems with the sensory environment, difficulties when placed with inappropriate peers and general pressures of mainstream classrooms), tensions in school relationships (including problems with staff and peers, alongside a general lack of communication), and problems with staff responses (including a perceived lack of understanding of the girls' needs and a lack of appropriate support being provided, resulting in 'battles' between parents and schools). Conclusions: The themes and subthemes that emerged from the interviews were not unique to autistic girls. Indeed, issues such as inappropriate school environments, a lack of staff understanding and breakdowns in relationships have been repeatedly raised by parents and young autistic people (mostly boys) in other studies, albeit in different environments. Nevertheless, the results highlight that more needs to be done to positively influence the direction of the girls' educational journeys. Implications: To improve the inclusion of autistic girls, it is recommended that educational establishments be proactive in developing inclusive environments, build positive relationships (both in and outside of the classroom) and, if exclusion is unavoidable, better support students both before and after the process.